Acute Lymphoblastic Leukemia following Lenalidomide Maintenance for Multiple Myeloma: Two Cases with Unexpected Presentation and Good Prognostic Features. (12th February 2018) - Khan, Abdullah M.; Muzaffar, Jameel; Murthy, Hermant; Wingard, John R.; Moreb, Jan S.
Abstract : Lenalidomide maintenance following autologous stem cell transplant (ASCT) is considered the standard of care for eligible patients with multiple myeloma (MM). A recent meta-analysis has provided additional evidence that lenalidomide maintenance is associated with a higher incidence of second primary malignancies, including both hematologic and solid malignancies. Acute lymphoblastic leukemia (ALL) as a second primary malignancy is rarely described in the literature. Herein, we describe two patients with MM treated with induction therapy, ASCT, and lenalidomide maintenance that experienced cytopenias while on maintenance. ALL was unexpectedly diagnosed on bone marrow biopsy. One patient was diagnosed on routine biopsy performed as part of requirements of the clinical trial. Both patients had B-cell ALL, without known poor risk cytogenetics, and were managed with standard induction therapies resulting in complete remission. We also reviewed the literature for similar cases of secondary ALL (sALL) in MM patients exposed to immunomodulatory drugs (IMiDs). In conclusion, persistent cytopenias in responding MM patients receiving IMiDs maintenance should be an indication for bone marrow biopsy. Patients develop sALL after median of 32.5 months (range, 20–84) from being on lenalidomide or thalidomide maintenance, often presenting with cytopenias, display low tolerance to chemotherapy, but remission can often be achieved.